Application and Analysis of Computer Vision Algorithms in Graphics and Image Processing - Zhou, Xiangming (International Journal of Informatics and Information Systems, 2023)
After decades of research by researchers, there have been many mature algorithms and systems that can meet the requirements for the application of computer vision algorithms in many fields. There are applications of computer algorithms in many industries, such as car navigation, video detection, industrial production and other industries. Most industries have synchronization requirements in terms of time, that is, real-time. Because of the limitation on the amount of calculation, many realtime vision systems will use the local window algorithm, but the image quality generated by the local algorithm and the image quality generated by the global algorithm have a large gap. According to the latest research results, if you use precisely adjusted matching calculation and collection methods, the local algorithm is as good as the global algorithm in terms of matching rate. This article mainly takes UAV as the research object, and studies the UAV's processing function of graphics and image based on computer vision algorithm. The research content mainly includes the single passage of the UAV in different environments of straight lines, corners, and slopes, and the passage of the UAV in the overall process. Through the application of computer vision algorithms in the UAV's graphics and image processing process, the experimental data is analyzed and the corresponding conclusions are drawn.